Understanding anthropological understanding: For a merological anthropology - Zeitlyn, D; Zeitlyn, D (SAGE Publications, 2009)
In this article I argue for a merological anthropology in which ideas of 'partiality' and 'practical adequacy' provide a way out of the impasse of relativism which is implied by postmodernism and the related abandonment of a concern with 'truth'. Ideas such as 'aptness' and 'faithfulness' enable us to re-establish empirical foundations without having to espouse a simple realism which has been rightly criticized. Ideas taken from ethnomethodology, particularly the way we bootstrap from 'practical adequacy' to 'warrants for confidence', point to a merological anthropology in which we recognize that we do not and cannot know everything, but that we can have reasons for being confident in the little we know. © 2009 SAGE Publications.